Insects found in different ages of coconut viridis variety in Sri Tiga Village, Banyuasin District, South Sumatra, Indonesia - ERISE ANGGRAINI; TESSIA MASNITA SINAGA; CHANDRA IRSAN; SITI HERLINDA; AHMAD MUSLIM; HARMAN HAMIDSON; MARLIN SEFRILA; ASTUTI KURNIANINGSIH; DESI ARYANI; MIRZA ANTONI; ZAHLUL IKHSAN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Anggraini E, Sinaga TM, Irsan C, Herlinda S, Muslim A, Hamidson H, Sefrila M, Kurnianingsih A, Aryani D, Antoni M, Ikhsan Z. 2024. Insects found in different ages of coconut viridis variety in Sri Tiga Village, Banyuasin District, South Sumatra, Indonesia. Biodiversitas 25: 2637-2647. Coconut (Cocos nucifera L.) is a high-value export commodity and has promising potential on the global market. The existence of insect species is very important in coconut cultivation. The coexistence of insects and plants is interconnected because plants provide habitat and food sources for insects. However, the correlation between plants and insects still needs to be discovered to many people. Therefore, a comprehensive assessment of insect biodiversity in an environment is important to be carried out. This study revealed the structure of the insect community associated with coconut plants and weeds around coconut trees. Therefore, this is a novel and pioneering study that aims to determine the insects associated with coconut plants. This study was conducted by surveying community-owned coconut plantations in Sri Tiga Village, Sumber Marga Telang Sub-district, Banyuasin District, South Sumatera, Indonesia. The observation was carried out during July and September of 2023. The data-gathering process involved identifying three coconut plantations with varying ages of coconut trees (8, 5, and 2 years old). Data collection was carried out using the purposive sampling method by direct observations and using traps such as insect nets, light traps, and pheromone traps. Collected specimens were identified using a microscope in the Laboratory of Entomology, Department of Plant Pests and Disease, Faculty of Agriculture, Universitas Sriwijaya. The results of this study found 12 insect species in coconut trees, namely Oryctes rhinoceros Linnaeus 1758, Aspidiotus sp., Nipaecoccus nipae Maskell 1893, Aleurocanthus sp., Apis cerana Fabricius 1793, Cotesia congregata Say 1836, Dolichoderus thoracicus Smith 1860, Oecophylla smaragdina Fabricus 1775, Provespa sp., Pteroma pendula de Joannis 1929, Metura sp., Metisa plana Walker 1883. The predominant insect pests identified were Aspidiotus sp., N. nipae, and Aleurocanthus sp. Furthermore, the most predominant insects that served as insect scavengers were Polyrhachis sp. and O. smaragdina. Meanwhile, in the weeds around coconut trees, there were found six insect species, namely Aulacophora lewisii Baly 1866, Eumorphus westwoodi Guérin 1858, Mactrotermes sp., Conocephalus sp., Dianemobius sp., and Tettigidea sp.